Urban tourism in Tabriz, Iran: An analysis of the domestic tourism market / Habib Zeinizadeh - Habib , Zeinizadeh (2017)
Domestic tourism in the urban areas of Iran has grown significantly in the past two decades. This rapid growth poses great potential for urban regeneration and development of the local economy. The steady stream of urban tourists from all over the country arose not because of active promotion but as a result of growing demand for travel. However, an understanding of the urban tourists‟ characteristics would lead to better organization and management in this regard. Availability of information is an important factor for effective planning and management of the tourism market. In line with this argument, understanding and analyzing the characteristics of tourist's to Tabriz metropolitan, a city in northwest Iran, is essential to develop appropriate strategies and effective planning in the development of urban tourism in the domestic tourism sector of Tabriz. This study examined the dominant features and characteristics of the domestic tourism market in Tabriz, and studied the motives, behavior, needs, desires and satisfaction of tourists on tourism facilities and services. The main finding of this study has shown that there is a significant relationship between satisfaction from destination and the socio-demographic variables. The results also indicated that recreation was the main reason for tourists visiting Tabriz whilst historic and cultural attractions and pleasant climate were the most important factors affecting urban tourists‟ behavior. The family pattern of travel, lower income class, distance of origin to destination, choice of summer season for traveling, and low expenditure composed the main components of domestic tourism which have direct effects on urban tourism behavior in Tabriz metropolitan.